Taming access control security: extending capabilities using the views relationship - Markiewicz, Marcus E.; Lucena, Carlos J. P.; Cowan, Donald D. (Software, practice & experience, 2002)
The ‘views’ relationship indicates how an object‐oriented design can be clearly separated into objects and their corresponding interface. This paper uses the concept of ‘views’ in order to achieve full separation between the application and the security policy in the design and implementation. The result is achieved by providing a model for capabilities using ‘views’ that is richer than the traditional capability model. In addition, a distributed access control model is shown to be effective through the use of Secure Object Communication Channels (SOCCs) to allow for secure connections at the object level. This security is applicable in the e‐commerce application domain, bringing security directly to the application ion level. Copyright © 2002 John Wiley & Sons, Ltd.